Abatement of hazardous materials and biomass waste via pyrolysis and co-pyrolysis for environmental sustainability and circular economy. (1st June 2021) - Chew, Kit Wayne; Chia, Shir Reen; Chia, Wen Yi; Cheah, Wai Yan; Munawaroh, Heli Siti Halimatul; Ong, Wee-Jun
Abstract: The remarkable journey of progression of mankind has created various impacts in the form of polluted environment, amassed heavy metals and depleting resources. This alarming situation demands sustainable energy resources and approaches to deal with these environmental hazards and power deficit. Pyrolysis and co-pyrolysis address both energy and environmental issues caused by civilization and industrialization. The processes use hazardous waste materials including waste tires, plastic and medical waste, and biomass waste such as livestock waste and agricultural waste as feedstock to produce gas, char and pyrolysis oil for energy production. Usage of hazardous materials as pyrolysis and co-pyrolysis feedstock reduces disposal of harmful substances into environment, reducing occurrence of soil and water pollution, and substituting the non-renewable feedstock, fossil fuels. As compared to combustion, pyrolysis and co-pyrolysis have less emission of air pollutants and act as alternative options to landfill disposal and incineration for hazardous materials and biomass waste. Hence, stabilizing heavy metals and solving the energy and waste management problems. This review discusses the pyrolysis and co-pyrolysis of biomass and harmful wastes to strive towards circular economy and eco-friendly, cleaner energy with minimum waste disposal, reducing negative impact on the planet and creating future possibilities. Graphical abstract: Image 1 Highlights: Hazardous wastes are potential feedstock for pyrolysis and co-pyrolysis. Pyrolysis and co-pyrolysis are applied to convert waste materials into energy. Pyrolysis makes waste-free future and transition to the circular economy possible. Detailed studies on reaction mechanism and optimization of parameters are needed.